Vanilla ribeiroi Hoehne (Orchidaceae: Vanilloideae): notes on taxonomy and geographical distribution - Engels, Mathias Erich; Koch, Ana Kelly (Phytotaxa, 2021)
Vanilla materials collected during botanical explorations in the Northern region of the Mato Grosso State and the South of Pará State, Brazil were identified as V. ribeiroi. An elusive species that was originally described at the beginning of the 20th century, as part of the Rondon Commission. Vanilla ribeiroi is recircumbscribed on the basis of the original and fresh materials, an epitype is designed, and the distribution of the species is extended.